Adrenergic effects on exocrine secretion of rat submandibular epidermal growth factor. Issue 11 (November 1984) - Olsen, P S; Kirkegaard, P; Poulsen, S S; Nexø, E
Abstract : The present study was undertaken to investigate the effect of alpha- and beta-adrenergic agonists on secretion of epidermal growth factor (EGF) from the rat submandibular glands and to test the possibility of intestinal absorption of EGF. Alpha-adrenergic agonists increased the concentration of salivary EGF by approximately a hundred times, while the serum concentration of EGF was unchanged. The contents of EGF in the submandibular glands decreased upon administration of the alpha-adrenergic agonist noradrenaline, and this was confirmed on immunohistochemical investigation of the glands. Beta-adrenergic agonists had no effect on secretion of EGF from the submandibular glands. Intestinal absorption of EGF could not be confirmed, as stimulation by noradrenaline with free passage of saliva to the gastrointestinal tract and intrajejunal infusion of EGF had no influence on the concentration of EGF in serum. This study shows that alpha-adrenergic agonists stimulate exocrine secretion of submandibular EGF and that EGF in physiological amounts are not absorbed in the gastrointestinal tract.